A28: Description of the Juvenile Localized Scleroderma Subgroup of the CARRA Registry. Issue 11 (March 2014) - Wu, Eveline Y.; Li, Suzanne C.; Torok, Kathryn S.; Virkud, Yamini; Fuhlbrigge, Robert; Rabinovich, C. Egla; ,
Abstract : Background/Purpose: Localized scleroderma (LS) is a chronic inflammatory and fibrosing skin disease. We present baseline data on the juvenile LS (jLS) cohort from the Childhood Arthritis and Rheumatology Research Alliance (CARRA) registry, a multicenter observational pediatric rheumatic disease registry. Methods: Descriptive statistics were used for demographic, clinical and laboratory features. Data analysis included the two‐sample t‐test, chi‐square test, Fisher's exact test, and analysis of variance as appropriate. Results: Of 259 children in the database, 78% were female and 81% were Caucasian. Mean age at onset was 8.3 yr (± 4.2). Mean age at first pediatric rheumatology (PRH) evaluation was 9.5 yr (± 4.2), yet 37% had ≥5 yr delay from onset to first PRH visit. Linear scleroderma (LiS) was the most common subtype (54%), followed by circumscribed morphea (CM) (15%), generalized morphea (GM) (8%), eosinophilic fasciitis (2%), and pansclerotic morphea (1%). 20% of children had mixed subtype, and LiS‐CM was the most frequent combination (60%). Among LiS patients with face‐scalp localization (40%), neurologic and ocular diseases were reported in 7% and 4%, respectively. ANA positivity was found in 50% tested and was not associated with subtype, age at onset, extracutaneous manifestations, or features of disease damage. Children with new lesions were more likely to have an elevated creatine kinase (CK) (p=0.02) or aldolase (p=0.02); muscle atrophy (p=0.04) and extremity shortening (p=0.02) were also associated with an elevated CK. Children with any functional limitation (baseline worst ever ACR functional class II, III, and IV) (28%) had earlier first PRH visit (mean 0.88 yr ± 0.89) compared to those without limitation (class I) (mean 1.4 yr ± 1.8, p=0.03). The association was also significant when evaluating ≥1 yr (p=0.04), ≥2 yr (p=0.02), and ≥5 yr delay (p=0.02) in first PRH visit. Poorer function also correlated with presence of muscle atrophy, joint contracture, and extremity shortening (all p<0.001). Medications used are listed below. 1 Conclusion: In the CARRA registry, jLS occurred more frequently in females and Caucasians. LiS was the most common subtype. More than 1/3 of children had a ≥ 5 yr delay from symptom onset to PRH referral. Children without limitation are referred later, highlighting the insidious onset and need for educating referring providers. There is significant morbidity, with 28% of children reporting functional limitations. Poorer function correlated with disease damage, specifically muscle atrophy, joint contracture, and limb shortening. An elevated CK or aldolase was associated with new lesions, suggesting possible use as disease activity markers. CK elevation, associated with muscle atrophy and limb shortening, may also predict muscle involvement. Subcutaneous and oral MTX and pulse and long‐term daily corticosteroids are the most commonly used medications, followed by MMF.